Hypothesis‐driven investigations of diverse pharmacological targets in two mouse models of autism - Rhine, Maya A. (Autism Res, 2019)
Autism spectrum disorder is a neurodevelopmental syndrome diagnosed primarily by persistent deficits in social interactions and communication, unusual sensory reactivity, motor stereotypies, repetitive behaviors, and restricted interests. No FDA‐approved medical treatments exist for the diagnostic symptoms of autism. Here we interrogate multiple pharmacological targets in two distinct mouse models that incorporate well‐replicated autism‐relevant behavioral phenotypes. Compounds that modify inhibitory or excitatory neurotransmission were selected to address hypotheses based on previously published biological abnormalities in each model. Shank3B is a genetic model of a mutation found in autism and Phelan‐McDermid syndrome, in which deficits in excitatory neurotransmission and synaptic plasticity have been reported. BTBR is an inbred strain model of forms of idiopathic autism in which reduced inhibitory neurotransmission and excessive mTOR signaling have been reported. The GABA‐A receptor agonist gaboxadol significantly reduced repetitive self‐grooming in three independent cohorts of BTBR. The TrkB receptor agonist 7,8‐DHF improved spatial learning in Shank3B mice, and reversed aspects of social deficits in BTBR. CX546, a positive allosteric modulator of the glutamatergic AMPA receptor, and d‐cycloserine, a partial agonist of the glycine site on the glutamatergic NMDA receptor, did not rescue aberrant behaviors in Shank3B mice. The mTOR inhibitor rapamycin did not ameliorate social deficits or repetitive behavior in BTBR mice. Comparison of positive and negative pharmacological outcomes, on multiple phenotypes, evaluated for replicability across independent cohorts, enhances the translational value of mouse models of autism for therapeutic discovery. GABA agonists present opportunities for personalized interventions to treat components of autism spectrum disorder. Autism Res 2019, 12: 401–421 © 2019 The Authors. Autism Research published by International Society for Autism Research published by Wiley Periodicals, Inc. LAY SUMMARY: Many of the risk genes for autism impair synapses, the connections between nerve cells in the brain. A drug that reverses the synaptic effects of a mutation could offer a precision therapy. Combining pharmacological and behavioral therapies could reduce symptoms and improve the quality of life for people with autism. Here we report reductions in repetitive behavior by a GABA‐A receptor agonist, gaboxadol, and improvements in social and cognitive behaviors by a TrkB receptor agonist, in mouse models of autism.